PRINSIP-PRINSIP DAN MODEL DESAIN DALAM PEMBELAJARAN - Samsudin Samsudin; Junaidin Junaidin (Prodi PAI STIT Sunan Giri Bima, 2021)
This article aims to discuss the principles and design models in learning and using a library approach. This paper is useful to help determine a learning model. There are several things that need to be considered before choosing a learning model, including identifying problems and setting learning objectives, determining and analyzing student character, identifying material and analyzing components of learning tasks related to achieving learning objectives, setting specific learning objectives for students, making systematics delivery of learning materials systematically and logically, designing learning strategies, determining methods for delivering subject matter, developing evaluation instruments, selecting sources that can support learning activities.